Natural Convection in a Porous Square Enclosure Containing an Oval-Shaped Heat Source - คํามุงคุณ ภัทรพร; ไวท์ยางกูร สุพจน์ (KKU Science Journal, 2016)
In this paper, we present the numerical study of natural convection in a porous square enclosure containing an oval-shaped heat source. The finite element method is used to solve this problem. The fluid properties are laminar, viscous and incompressible flow, for steady state in a porous square enclosure containing an oval-shaped heat source. The boundary conditions of the side walls for the square enclosure are cold while the oval-shaped is heated. The Darcymodified Rayleigh number is between 10 and 103 . The problems studied are the behavior and distribution of isotherms, streamlines and heatlines when the value of Darcy-modified Rayleigh number and the size of the heat source are different.